The methodology of Irfan 'Abdul Hamid Fattah in the study of religion with special reference to his book on al-Yahudiyyah: An analytical study - Shehu, Fatmir Mehdi (2015)
The legacy of 'Irfan 'Abdul Hamid Fattah, a contemporary Muslim thinker, on the study of religion, is unknown to the world of academia, except to a small group of intellectuals and especially his students. Hence, it is very significant to undertake a study on his contributions towards the Muslim scholarship in study of religion. This paper investigates Fattah’s methodology in the study of Judaism, its historical development and theological doctrines and his paradigm shift to inter-religious dialogue with special reference to his book on al-Yahudiyyah: 'Ardun Tarikhi wa al-Harakat al-Hadiythah fi al-Yahudiyyah. Descriptive and analytical methods will be employed throughout the study. The findings of this research will add to the body of modern comparative religion the insights of the original work of a Muslim thinker and theologian in the study of Judaism. It will as well, enhance our understanding of contemporary Muslim approaches to the study of other religions.